Risk of the development of chronic kidney diseases versus nutritional profile of hospitalized patients (Research, Society and Development, 2021)
Correlate nutritional status with the risk of developing chronic kidney disease. Data collection was performed at a hospital in Fortaleza-CE. Nutritional assessment was carried out in adults and elderly with the application of two questionnaires, called: Screening For Occult Renal Disease (SCORED) and Food Frequency Questionnaire (FFQ), along with biochemical tests and water intake. It is noteworthy that the collected data were tabulated in Microsoft Excel version 2016, statistical tests were performed for the reliability of the correlations in search of a cross between nutritional profile and the development of CKD in hospitalized patients. The sample consisted of 260 volunteers, 58.1% male, with the highest percentage being 34.6% (90) aged between 40-69, where 40% (104) of the sample is black and with per capita income median less than a minimum wage. As for the Body Mass Index (BMI), 15.8% (41) of adult patients of both sexes are eutrophic, whereas the percentage found for elderly patients was 20.4% (53) classified as thin. As verified by the SCORED questionnaire, 75.4% of the evaluated have the risk of developing CKD. As for biomarkers, urea values ​​were inadequate in 62.7% of those evaluated and 42.7% had stage 2 GFR. It is extremely important to monitor and frequently reassess patients by professionals. Nutritional monitoring aims to promote a better quality of life, minimizing nutritional risks in the hospital environment.